Therapeutic effects of internal fixation with support plates and cannulated screws via the posterolateral approach on supination external rotation stage IV ankle fracture - Liu, Zhongbing (Pak J Med Sci, 2020)
OBJECTIVE: To evaluate the therapeutic effects of internal fixation with support plates and cannulated screws via the posterolateral approach on supination external rotation stage IV ankle fracture. METHODS: Eighty-five patients with SER-IV° ankle fracture and large posterior malleolar fracture treated from June 2016 to June 2018 in our hospital, were randomly divided into a support plate group (n=47) and a cannulated screw group (n=38). The treatment outcomes were compared regarding surgical time, amount of bleeding, time of fracture healing, postoperative complications, as well as the American Orthopedic Foot and Ankle Society (AOFAS) Ankle-Hindfoot Score and excellent rate one year later. RESULTS: The surgical time and intraoperative blood loss of cannulated screw group were significantly lower than those of support plate group (P<0.05). There were four cases of posterior lateral incision redness complicated with obvious bloody exudation in support plate group on the postoperative 2nd day. One case developed into superficial incision infection subsequently, and one case suffered from deep infection. After dressing and treatment with sensitive antibiotics, stitch removal was delayed, and primary healing was obtained. In cannulated screw group, there were two cases of posterior lateral incision redness complicated with obvious bloody exudation on the postoperative 3rd day, without skin incision infection. One case had cannulated screw loosening two months after surgery, and the posterior malleolar fracture block was slightly displaced. The incidence of surgical complications in support plate and cannulated screw groups were 8.51% and 7.89%, respectively (P>0.05). The AOFAS scores of cannulated screw ((81.71 ± 12.39) points) and support plate groups ((86.62 ± 10.12) points) were significantly different (P<0.05). CONCLUSION: For patients with posterior malleolar fracture or osteoporosis, fixation using support plate is recommended. Cannulated screw fixation is suitable for for patients with poor conditions of skin soft tissues or basic diseases such as diabetes intolerant to long surgery.